“Easy Rent” business plan : a household appliances renting service - Vian, João Maria Matos Salvador (2018)
The constant increase of mobility among the world population and the increase importance of the feeling of convenience on younger generations are changing the way people live, think and act. Certain kind of services are nowadays even more valued due to the level of experience they transmit to those who use it, and that is one of the reasons I chose to develop a business plan about a service, on this case, a household appliances renting service called “Easy Rent”. One of the most common ways of mobility around the world are students exchange programmes, and because I did it and had the opportunity to study six months on a foreigner country, my main focus on this plan has been on exchange students. The main goal of this business plan is to understand the level of acceptance towards this innovative business idea and to determine if the business itself is financially viable or not. To reach this goal, there were two major strategies that were developed through the plan: (1) The focus on three different areas of the business: Marketing and Communication, Logistics and Financial; (2) The development of an online survey with a representative population sample of 190 respondents, whose responses were statistically analysed on RStudio program. After all the research, planning and analysis, it is possible to conclude that there is in fact a positive awareness regarding “Easy Rent” service and that the business itself is financially viable on the long-term.